Detection of bovine Herpesvirus type 5 in formalin-fixed, paraffin-embedded bovine brain by PCR: a useful adjunct to conventional tissue-based diagnostic test of bovine encephalitis - Ferrari, H. F. [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Rahal, Paula [UNESP]; Cardoso, T. C. [UNESP] (Elsevier B.V., 2007)
The aim of this study was to evaluate the application of PCR technique for the detection of BoHV-5 in routinely formalin-fixed, paraffin-embedded brain tissues in 20 naturally infected calves affected by fatal meningoencephalitis. Brains were divided into two halves, one kept fresh for virus isolation and PCR assay, targeting the glycoprotein C gene from BoHV-5 genome. The other half brain, corresponding to posterior cortex region, was submitted to formalin fixation and embedded into paraffin blocks for microscopic evaluation and total DNA isolation. Most of the slides showed severe multifocal non-supurative encephalitis with neuronal degeneration, neurophagia, and no acidophilic intranuclear inclusions could be found in neurons and glial. The 20 fresh samples were confirmed, by virus isolation and PCR assay, as having the BoHV-5 virus and, respective glicoprotein C sequence, while 15 of 20 formalin-fixed, paraffin-embedded samples were considered positive for the same analysis. The results revealed the first description of PCR efficiency, applied to formalin-fixed, paraffin-embedded brain collected from naturally infected calves, improving the detection of BoHV-5 from archival samples in South America. (c) 2007 Published by Elsevier B.V.
Keywords: bovine Herpesvirus type 5; BoHV-5; PCR; cell culture; formalin-fixed paraffin-embedded tissues